A Hybrid Multi-Attribute Framework for Optimizing Turnaround Inspection Scope in Oil and Gas Facilities (London Journal of Engineering Research, 2025)
Purpose – The purpose of this paper is to support operating facilities in identifying the appropriate and adequate initial turnaround (TA) inspection scope strategies and prioritizing operation, maintenance & engineering efforts to help deliver production operational targets by limiting the TA on to the equipment that internal inspection is necessary and avoid unnecessary replacement of internal parts (e.g., catalysts, desiccant, etc.) due to exposing the equipment to internal inspection. Furthermore, identify the inspections that can be performed non-intrusively and online, which can shorten the TA duration, minimize business interruption, and maximize plant availability.Design/methodology/approach – The case study was conducted using one of the most widely deployed risk models in the oil and gas industry, where a full assessment was performed on an offshore gas-producing platform.
Keywords: Gyroscopic effect; Straight cylindrical gears; Dynamic characteristics; Vortex